2021
DOI: 10.3390/ph14050458
|View full text |Cite
|
Sign up to set email alerts
|

Some Candidate Drugs for Pharmacotherapy of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD; progressive neurodegenerative disorder) is associated with cognitive and functional impairment with accompanying neuropsychiatric symptoms. The available pharmacological treatment is of a symptomatic nature and, as such, it does not modify the cause of AD. The currently used drugs to enhance cognition include an N-methyl-d-aspartate receptor antagonist (memantine) and cholinesterase inhibitors. The PUBMED, Medical Subject Heading and Clinical Trials databases were used for searching re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 187 publications
0
21
0
Order By: Relevance
“…In this regard, in a combinatory therapy with 3 or 4 drugs (anticholinergics, memantine, aducanumab, sodium oligomannate (GV-971), antiinflammatories) it may be interesting to add a drug such as metformin, which may be key in improving hypometabolism and increasing glucose uptake in the brain. For this reason, metformin (or other antidiabetic drugs) can provide added value by increasing glucose transport to neurons and increasing ATP levels [65,[149][150][151][152][153]. Thus, based on literature, metformin can be used to inhibit dementia progression and can be a novel therapeutic medication for strengthening LOAD-related cognitive dysfunction [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, in a combinatory therapy with 3 or 4 drugs (anticholinergics, memantine, aducanumab, sodium oligomannate (GV-971), antiinflammatories) it may be interesting to add a drug such as metformin, which may be key in improving hypometabolism and increasing glucose uptake in the brain. For this reason, metformin (or other antidiabetic drugs) can provide added value by increasing glucose transport to neurons and increasing ATP levels [65,[149][150][151][152][153]. Thus, based on literature, metformin can be used to inhibit dementia progression and can be a novel therapeutic medication for strengthening LOAD-related cognitive dysfunction [65].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that metformin decreases the levels of IL-1β and IL-6 in APP/PS1 mice [76]. In addition, different studies have highlighted the anti-inflammatory and antioxidant function of metformin, with several pathways playing a key role in the activation of AMPK [147][148][149][150][151][152]. In certain cases, metformin suppresses inflammation and decreases or removes inflammatory factors largely by dependent pathways and often independently of AMPK at the cellular level and elsewhere at the systemic level [148,149].…”
Section: Metformin Effects On Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been very limited efficacy in preventing the onset of some new memory-related symptoms with memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist, cholinesterase inhibiters such as donepezil, and a recently approved combination of the two classes (Miziak et al, 2021). However, there are no current interventions which treat the etiology of or even prevent the progression of AD, in spite of many studies and clinical trials (i.e., Farlow et al, 2012;Ostrowitzki et al, 2017;Cummings et al, 2018;Egan et al, 2019;Haass and Levin, 2019).…”
Section: Current Pharmacological Therapiesmentioning
confidence: 99%
“…This leads to the possibility of mirtazapine to be administered in a combination therapy for AD patients, eventually leading to better outcomes by targeting different signaling pathways [ 114 , 121 ]. Additionally, the combination of antipsychotics (such as risperidone and quetiapine) and mirtazapine may be also observed in AD therapeutic regimens [ 122 , 123 ].…”
Section: Mirtazapinementioning
confidence: 99%